The use of silver nanoparticles in pigs - An invited review - N Hodkovicova; M Machacek; J Cahova; J Consolacion; A Siwicki; Z Pejsak; M Svoboda (Veterinární Medicína)
Silver nanoparticles (AgNPs) have attracted significant interest in veterinary medicine due to their unique properties, including enhanced stability, greater antimicrobial efficacy, and reduced toxicity compared to traditional silver salts. Their applications span various areas of veterinary practice, such as dermatology, wound management, infection prevention, drug delivery, and disinfection. This review explores their use in pigs, highlighting their role as feed additives to prevent diarrhoea, as antibacterial agents in semen extenders, and veterinary dermatology. AgNPs possess broad-spectrum antibacterial activity against both Gram-positive and Gram-negative bacteria, positioning them as a promising alternative to antibiotics in addressing antibiotic resistance. Additionally, AgNPs have shown antiviral potential, though the exact mechanism of action remains unclear. The review examines the antibacterial and antiviral properties of AgNPs, their utility in facility sanitation, and their potential toxicity to pigs. While AgNPs offer significant benefits in veterinary applications, concerns about their toxicity persist. Efforts to reduce this toxicity, such as surface modifications or combining AgNPs with other substances, are under investigation. Further research is essential to fully understand the potential applications and safety of AgNPs in pig medicine.